Emphysematous gastritis - Ryosuke Takase (Wiley, 2021)
Abstract An 89‐year‐old woman who had type 2 diabetes mellitus suddenly presented with abdominal pain. Abdominal computed tomography showed thickening of the wall and intramural gas in the gastric hilum, suggesting emphysematous gastritis. The patient underwent treatment with a proton‐pump inhibitor and broad‐spectrum antibacterial agents.